2006
DOI: 10.1021/ac052218f
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Antiparallel G-Quadruplex Structure in Human Telomeres by Using Two-Photon Excitation Fluorescence Lifetime Imaging Microscopy of the 3,6-Bis(1-methyl-4-vinylpyridinium)carbazole Diiodide Molecule

Abstract: Different G-quadruplex structures for the human telomeric sequence d(T2AG3)4 in vitro have been documented in the presence of sodium and potassium. Verification of the G-quadruplex structures in human telomeres in vivo is the main issue in establishing the biological function of the G-quadruplex structures in telomeres as well as the development of anticancer agents. Here we have applied two-photon excitation fluorescence lifetime imaging microscopy to measure the fluorescence lifetime of the BMVC molecule upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 26 publications
1
52
0
1
Order By: Relevance
“…[16][17][18] We have synthesized a fluorescent molecule, 3,6-bis (1-methyl-4-vinylpyridinium) carbazole diiodide (BMVC), to verify the presence of G4 structure in the human telomeres of metaphase chromosomes of nasopharyngeal carcinoma KJ-1 cells by using fluorescence lifetime imaging microscopy (FLIM). 19 Our finding was very recently confirmed by immunofluorescence for binder of G-quadruplex (BG4) on metaphase chromosomes isolated from Hela cancer cells. 20 They found that the majoriy (∼75%) of BG4 foci were present outside the telomeres.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…[16][17][18] We have synthesized a fluorescent molecule, 3,6-bis (1-methyl-4-vinylpyridinium) carbazole diiodide (BMVC), to verify the presence of G4 structure in the human telomeres of metaphase chromosomes of nasopharyngeal carcinoma KJ-1 cells by using fluorescence lifetime imaging microscopy (FLIM). 19 Our finding was very recently confirmed by immunofluorescence for binder of G-quadruplex (BG4) on metaphase chromosomes isolated from Hela cancer cells. 20 They found that the majoriy (∼75%) of BG4 foci were present outside the telomeres.…”
Section: Introductionsupporting
confidence: 64%
“…19 Here o-BMVC is a better fluorescence probe for differentiating the G4 structures from duplexes than BMVC because o-BMVC has a large contrast of decay time, binding affinity, and fluorescent intensity between the G4 structures and the duplexes. To further test the detecting limit of the G4 structure revealed by o-BMVC, we have conducted competition analysis by mixing 30 μM of LD12 with various concentrations of HT23 using FLIM.…”
mentioning
confidence: 99%
“…Gquadruplex structures have been shown to exist in vivo in Stylonychia lemnae macronuclei [24], and recently in human cells [25]. In a paragraph below we shall discuss the G-quadruplex structures and their implication in telomere maintenance.…”
Section: Telomeric Dnamentioning
confidence: 99%
“…Any other combination of less than four pyridiniums seems to significantly reduce quadruplex binding. It has been recently reported that tetramethylpyridiniumporphyrazines (TMPyPz) (25)(26) bind strongly to quadruplexes, selectively inducing the antiparallel conformer [226]. TMPyPz are tetracationic phthalocyanine azaanalogues in which four pyridine moieties substitute the four benzene moieties in the macrocycle periphery [227].…”
Section: Surface Plasmon Resonancementioning
confidence: 99%
“…Significant increase of fluorescence yield and distinctive fluorescence emissions of the 3,6-bis(1-methyl-4-vinylpyridinium) carbazole diiodide (BMVC) upon binding to various DNA structures allowed us not only to verify for the first time the presence of the G-quadruplex (G4) structure in human telomeres for drug design [1,2] but also to distinguish cancer cells from normal cells for cancer diagnosis [3,4]. Investigation of BMVC in glycerol/water mixtures suggested that solvent viscosity plays a major role in determining the fluorescence quantum yield [5].…”
Section: Introductionmentioning
confidence: 99%